New Dawn : a 23 min documentary drama based on an ex-drug addict's life story - Buy, Grace Su Hui (2008)
New Dawn is a 23min documentary drama that recites the painful life story of an ex-drug addict, Don Wong, who is now the Director of the Highpoint Drug Rehabilitation Centre in Singapore, located at Amber Road.